Pengembangan Media Pembelajaran Menulis Teks Ceramah Berbasis Internet Bagi Siswa Kelas XI - Desi Nurasiah; Emah Khuzaemah; Indrya Mulyaningsih (Institut Agama Islam Negeri Curup, 2020)
Learning media includes alternative options that can represent what is less capable teachers speak through language, so that product embodiment can be expressed with the presence of learning media. This research aimed to produce an Internet-based learning medium that could help students write lecture texts according to aspects and proper linguistic structure. The text structure of the lecture included correct sentences, effectiveness of sentences, and punctuations. This research applied R&D (Research and Development) with a descriptive analysis technique. The development steps on the research included the preliminary stages or the analyses of studentsâ€™ needs and characteristics, the implementation stage of development (design draft) and the validation test phase by expert lecturers. The data were collected using observations with observation sheets as the instrument and documentation with data cards as the instrument. Observation sheets and data cards were deployed to determine students' writing mistakes on the effectiveness of the students' sentences and punctuations. Based on the error, it was needed the supporting tool through media Blogger Kahoot. Blogger Kahoot media referred to two tools having an association in the learning process. It represented a Blogger media as the material delivery and a Kahoot media as the evaluation stage. BloggerKahoot media had been validated by expert lecturers with the eligibility of content, language eligibility, presentation eligibility, and grafapia eligibility.Â The results of the validation demonstrated that the Blogger Kahoot learning media was worthy to use